Exploring the Impact of Dapagliflozin on Shock Therapy in Heart Failure Patients with Implantable Cardioverter Defibrillators: A Retrospective Cohort Study - Seyis, Sabri (Cardiology and Cardiovascular Medicine, 2024)
Background: Heart failure (HF) remains a leading cause of morbidity and mortality worldwide, with implantable cardioverter-defibrillators (ICDs) being crucial for managing life-threatening arrhythmias in these patients. Dapagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, has shown promise in improving cardiovascular outcomes in HF patients, yet its effects on those with ICDs have not been thoroughly explored. Methods: This retrospective cohort study analyzed health records from 74 heart failure patients with ICDs who were treated with Dapagliflozin alongside standard HF therapy. We compared these patients’ records before and after treatment with Dapagliflozin. Primary outcomes included the incidence of ICD shock therapy and arrhythmia episodes. Results: No significant difference was found between the number of shocks observed in the 6-month follow-up before dapagliflozin treatment and the number of shocks observed in the 6-month follow-up after dapagliflozin treatment (p=0.754). Also, VT episodes were similar(p=0.453). Conclusion: Dapagliflozin treatment in heart failure patients with ICDs has no adverse effects on arrhythmia episodes and ICD shock therapy. This aligns with the broader literature indicating dapagliflozin's role in reducing heart failure events and cardiovascular deaths without specifically addressing its impact on ICD shock occurrences.